2006
DOI: 10.1111/j.1365-2710.2006.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence: a comparison among patients with schizophrenia who were initiated on atypical antipsychotic agents

Abstract: Compared with risperidone, olanzapine seems to be better tolerated by patients as indicated by better treatment persistence. As such, initiation of olanzapine may increase the likelihood of sustaining control of symptoms of schizophrenia. Future research needs to provide a more comprehensive assessment of treatment persistence by considering other antipsychotic agents in the study and developing models to assess treatment persistence and switching as two interdependent competing risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Over the past two decades, interest has increased in studies on treatment persistence with antipsychotic agents (Lehman and Steinwachs 1998; Valenstein et al 2002; Lehman et al 2004; Lieberman et al 2005; Ren et al 2006). A number of studies have reported that poor treatment persistence with antipsychotic agents is a common problem among patients with schizophrenia (Docherty et al 2003; Tafesse et al 2003), which results in relapse of schizophrenic symptoms, increased outpatient visits, hospital admissions, and associated unnecessary medical expenses (Grogg et al 2002; Lacro et al 2002; Docherty et al 2003; Tafesse et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past two decades, interest has increased in studies on treatment persistence with antipsychotic agents (Lehman and Steinwachs 1998; Valenstein et al 2002; Lehman et al 2004; Lieberman et al 2005; Ren et al 2006). A number of studies have reported that poor treatment persistence with antipsychotic agents is a common problem among patients with schizophrenia (Docherty et al 2003; Tafesse et al 2003), which results in relapse of schizophrenic symptoms, increased outpatient visits, hospital admissions, and associated unnecessary medical expenses (Grogg et al 2002; Lacro et al 2002; Docherty et al 2003; Tafesse et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, the likelihood of sustaining control of schizophrenic symptoms depends on the persistence of treatment (Vanelli et al 2001; Menzin et al 2003). The importance of sustained treatment in the clinical management of schizophrenia, coupled with known differential side effects associated with typical and atypical antipsychotic agents (Kane 1996; Allison et al 1999; Leucht et al 1999; Leslie and Rosenheck 2001), has generated a lot of interest in comparing treatment persistence across antipsychotic agents (APA 1997; Lehman and Steinwachs 1998; VA 1998; Valenstein et al 2002; Docherty et al 2003; Lehman et al 2004; Lieberman et al 2005; Ren et al 2006). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al [41] assessed differences in persistence between groups of patients initiated on olanzapine (n ¼ 3570) or risperidone (n ¼ 3574) in the Veterans Administration system, based on the frequency of switching within the first 2 months of treatment. The results indicated that olanzapine use was associated with better persistence.…”
Section: Data Supporting Improved Compliance With New Antipsychotic Dmentioning
confidence: 99%
“…However, the likelihood of sustaining control of schizophrenic symptoms depends on treatment adherence with antipsychotic agents by the patients 3,4. The importance of sustained medication treatment in the management of schizophrenia, coupled with known differential side effects associated with typical and atypical antipsychotic agents,58 has generated a lot of interest in the development of pharmacy-based measures to compare the levels of treatment adherence across different antipsychotic agents 9–17…”
Section: Introductionmentioning
confidence: 99%